1999
DOI: 10.1148/radiology.211.1.r99ap35215
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Carcinoma: Thin-Section MR Imaging for Staging in 28 Patients

Abstract: Preoperative thin-section MR imaging accurately indicates the tumor stage of rectal cancer and depth of extramural tumor infiltration. It provides valuable information for identifying T3 tumors for preoperative adjuvant therapy in patients who are at high risk of failure of complete excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
257
4
14

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 418 publications
(285 citation statements)
references
References 28 publications
10
257
4
14
Order By: Relevance
“…Many studies have shown that the depth of extramural invasion, nodal involvement and CRM involvement are independent markers of poor prognosis (Cawthorn et al, 1986;Jass and Love, 1989;Adam et al, 1994;Hall et al, 1998) and selection for neoadjuvant therapy is being increasingly based on these. MRI performs particularly well over other modalities in the assessment of these parameters and studies have prospectively validated the technique for accuracy of depth of extramural spread and its ability to predict CRM involvement (Brown et al, 1999(Brown et al, , 2003a. By contrast, DRE (which depends on the subjective appreciation of tumour mobility or fixity) performs poorly, understaging 47% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies have shown that the depth of extramural invasion, nodal involvement and CRM involvement are independent markers of poor prognosis (Cawthorn et al, 1986;Jass and Love, 1989;Adam et al, 1994;Hall et al, 1998) and selection for neoadjuvant therapy is being increasingly based on these. MRI performs particularly well over other modalities in the assessment of these parameters and studies have prospectively validated the technique for accuracy of depth of extramural spread and its ability to predict CRM involvement (Brown et al, 1999(Brown et al, , 2003a. By contrast, DRE (which depends on the subjective appreciation of tumour mobility or fixity) performs poorly, understaging 47% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…T2-weighted MRI was performed (Brown et al, 1999). The tumour was staged according to the TNM classification and the maximum depth of extramural spread was recorded using criteria developed previously (Brown et al, 1999(Brown et al, , 2003b.…”
Section: Imaging Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…The rational for this is that MRI can predict the T and N stage of a rectal tumour more accurately than CT and is superior at identifying contiguous organ involvement, a threatened CRM or the presence of extra-mural vascular invasion, which may influence the decision to use neoadjuvant treatment [16][17][18].…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%